Cardiovascular disease risk in paediatric and young adult non-alcoholic fatty liver disease. Issue 3 (15th December 2022) - Simon, Tracey G; Roelstraete, Bjorn; Alkhouri, Naim; Hagström, Hannes; Sundström, Johan; Ludvigsson, Jonas F
Abstract : Objective: Longitudinal evidence is lacking regarding the long-term risk of major adverse cardiovascular events (MACE) in children and young adults with non-alcoholic fatty liver disease (NAFLD). Design: This nationwide cohort study included all Swedish children and young adults ≤25 years old with histologically confirmed NAFLD and without underlying cardiovascular disease (CVD) at baseline (1966–2016; n=699). NAFLD was defined from prospectively recorded histopathology, and further categorised as simple steatosis or non-alcoholic steatohepatitis (NASH). NAFLD patients were matched to ≤5 population controls without NAFLD or CVD (n=3353). Using Cox proportional hazards modelling, we calculated multivariable-adjusted HRs (aHRs) and 95% CIs for incident MACE (ie, ischaemic heart disease, stroke, congestive heart failure or cardiovascular mortality). In secondary analyses, we also explored rates of incident cardiac arrhythmias. Results: Over a median follow-up of 16.6 years, incident MACE was confirmed in 33 NAFLD patients and 52 controls. NAFLD patients had significantly higher rates of MACE than controls (3.1 vs 0.9/1000 person-years (PY); difference=2.1/1000 PY; aHR=2.33, 95% CI=1.43 to 3.78), including higher rates of ischaemic heart disease (difference=1.4/1000 PY; aHR=3.07, 95% CI 1.62 to 5.83) and congestive heart failure (difference=0.5/1000 PY; aHR=3.89, 95% CI=1.20 to 12.64). Rates of incident MACE outcomes appeared to be further augmented with NASH (aHR=5.27, 95% CI=1.96 to 14.19). In secondary analyses, NAFLD patients also had significantly higher rates of cardiac arrythmias (aHR=3.16, 95% CI=1.49 to 6.68). Conclusion: Compared with matched population controls, children and young adults with biopsy-proven NAFLD had significantly higher rates of incident MACE, including ischaemic heart disease and congestive heart failure. Research to better characterise cardiovascular risk in children and young adults with NAFLD should be prioritised.